2009
DOI: 10.1007/s12031-009-9185-8
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of GnRH and LHβ mRNA Expression in Cultured Rat Granulosa Cells

Abstract: We have recently demonstrated that the rat ovary expresses LHbeta, FSHbeta, and the common alpha subunit mRNA. In the present report, we studied the regulation of LHbeta and of gonadotropin-releasing hormone (GnRH) mRNA expression in granulosa cells that were isolated from immature rats treated with either estrogen or pregnant mare serum gonadotropin (PMSG). In both cell types, GnRH agonist treatment resulted in a decrease in LHbeta mRNA expression. However, only in cells derived from PMSG-treated rats, GnRH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
1
10
1
1
Order By: Relevance
“…It has been shown that this sequence is bound by a Smad3-Foxl2 heterodimer [29]. Though it is best known and studied in the pituitary, recent evidence suggests that the GnRH/GnRHR system is present in the ovary [30], [31]. However, the physiological implications of this are still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that this sequence is bound by a Smad3-Foxl2 heterodimer [29]. Though it is best known and studied in the pituitary, recent evidence suggests that the GnRH/GnRHR system is present in the ovary [30], [31]. However, the physiological implications of this are still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…However, we might assume that the presence of intraovarian GnRH causes LH release in the ovary (data not shown), as stated by Schirsman-Hildesheim et al [43]. These authors demonstrated that the ovarian LH might be synthesized in a heterologous/homologous way [43,44]. Therefore, these findings might imply the existence of a local GnRH-gonadotropin axis in the mammals ovary that might be involved in the processes leading to the continuity of the oestrous cycle, and might be responsible for the P 4 increase in the ovary incubation.…”
Section: Discussionmentioning
confidence: 68%
“…Because estrogen treatment decreases GnRH-1 mRNA levels in human luteal granulosa cells, a result reversed by estrogen antagonists [22], the observed SD increase in GnRH-1 mRNA in the present study (Figure 3) could be due to significantly lower estrogen levels, and lower GnRH-1 levels in the PT group may then be related to newly resumed estrogen production (Figures 2, 3). This is further strengthened by immunolocalization of GnRH protein in granulosa, especially luteal granulosa cells in hamsters, primates, and rats (Figure 4) [6, 16]. …”
Section: Discussionmentioning
confidence: 96%
“…Regulation of intraovarian gonadotropins is not fully understood; control may be local, by the hypothalamus, or the pituitary, or a combination of regulatory factors may act in concert. Indeed, ovarian GnRH, and ovarian or pituitary FSH can regulate ovarian LHβ mRNA expression in isolated rat granulosa cells [16]. The additional intraovarian spike of both gonadotropins during diestrus (Figure 2B, 2C) mirrors the peak in GnRH (Figure 2A), a pattern that does not mimic pituitary mRNA, but does suggest differential regulation in the ovary and the pituitary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation